Some Applications of Fuzzy Differential Subordination on Analytic Functions Connected with Lommel Function (European Journal of Pure and Applied Mathematics, 2025)
The findings of this study are connected with geometric function theory and were acquired by using Fuzzy subordination-based techniques in conjunction with the convolution concept and Lommel Function LMn,v. The first class introduced and investigated here is a generalized class of analytic functions. It is also shown that for particular choice of parameters for the new generalized class, the class of close-to-convex functions emerges. Using the properties of the convolution and subordination, certain characterization properties of this class are proved involving combinations of the functions from the class. Further, three more classes are defined in connection to this first class, developing new applications of Lommel function by using the fuzzy subordination technique and convolutions.
Keywords: Analytic function, Fuzzy set, Differential subordination, Lommel Function